Quantum Features of Radiation at Small-Angle Reﬂection by Crystals; Radiation from Relativistic Electrons in Periodic Structures (RREPS-19) - Korotchenko K. B. Konstantin Borisovich; Eykhorn Yu. L. Yury Leonidovich; Kunashenko Yu. P. Yuriy Petrovich; Lewandowski A. (General Radiation Properties from Relativistic Particles, 2019)
Title screen